Learning about particle dynamics through Interactive Physics software in engineering students - Taipe, Ciro (2020)
The research aimed to determine the effects of the Interactive Physics software on the dynamic learning of a particle in engineering students from the National University of Juliaca (Peru-2017), in order to optimize the academic performance of the students of the Professional School Textile and Clothing Engineering. The research design was quasi-experimental for the application of the Interactive Physics software. Seeking that the student interact in their learning process related to the application of Newton's laws in solving problems of particle dynamics. For the collection of information, the written test of knowledge of the dynamics of a particle has been used. The population was made up of students from the second semester of Textile and Apparel Engineering. The results indicate that 8% of the students in the experimental group are in the very good category in relation to the students in the 4% control group who are in the very good category.